Serbia’s New Growth Agenda : Increasing Exports - Frias, Jaime; Shimbov, Bojan; Davies, Elwyn; Ek, Colin (World Bank, Washington, DC, 2020)
Evidence from several countries reveals that nations that have open economies tend to enjoy higher income than those with closed economies (Lind and Ramondo 2018). Openness to hosting multinationalfirms can lead to firms in receiving countries acquiring new technology and skills (Harrison and Rodriguez-Clare 2010), and to productivity-enhancing spillovers, particularly through vertical commercial relationships between foreign and domestic suppliers. Learning by exporting offers positive knowledge externalities, and it comprises myriad ways in which exports can stimulate growth in productivity, including development of exporter capabilities, such as marketing new products; upgrading product quality; and acquiring expertise in managing customer relationships by dealing with foreign buyers. The value from knowledge spillovers and the promise of job creation are often seen as positive externalities and are usually brought in to justify policy interventions in the form of tax incentives, grants, and other concessions (access to land sites at minimal or low cost). It is often thought that spillovers from foreign firms are driven by transfers of technology and by learning about markets by exporting. Learning from foreign buyers is supposed to be channeled directly to the exporters or passed through to local suppliers and competitors in domestic markets. There is some evidence that in Serbia, the international competitiveness of domestic exporters has been diminishing, and government programs to support links with markets receive meager financial allocations. Recent successes in exports of manufactures have revealed the great potential of Serbia, but these have been driven by only a few firms, many of them foreign-owned. This has lowered expectations of inclusive and widespread growth. There is also a growing sense that government efforts to promote exports and attract export-oriented investment in Serbia have instead been directed to attracting foreign direct investment (FDI) at the expense of export promotion, which has not been particularly effective. A looming question has become whether the current policy mix for promoting competitive Serbian exports needs realignment.